TRAINING IN THE PROCESSING OF WASTE PAPER INTO RECYCLED PAPER WITH SELLING VALUE - Adrian K Tarigan; Eka Sihombing; Sondang Sidabutar (RADJA PUBLIKA, 2023)
Paper is one of the most common wastes produced by humans, this paper waste is often found in household activities as well as offices and schools. Processing recycling of paper can add many advantages including being able to reduce waste in the environment, save energy, reduce the impact of global warming and can also generate income. This recycled paper can also be used to make various handicraft products that can be made by people who have creative values and an artistic spirit. The works of this recycled paper can be used as home decoration knick-knacks, stationery and office equipment, You can also make unique and creative multi-purpose containers that housewives can be interested in. Apart from that, they can be used for materials for student craft assignments as well as school students. Paper waste management certainly requires more attention, this can be overcome by efforts to reduce it by converting paper waste into recycled paper which has a selling value and is useful.